1979
DOI: 10.1007/bf02684798
|View full text |Cite
|
Sign up to set email alerts
|

Sur la Conjugaison Différentiable des Difféomorphismes du Cercle a des Rotations

Abstract: Sur la conjugaison différentiable des difféomorphismes du cercle à des rotations Publications mathématiques de l'I.H.É.S., tome 49 (1979), p. 5-233 © Publications mathématiques de l'I.H.É.S., 1979, tous droits réservés. L'accès aux archives de la revue « Publications mathématiques de l'I.H.É.S. » (http:// www.ihes.fr/IHES/Publications/Publications.html) implique l'accord avec les conditions générales d'utilisation (http://www.numdam.org/conditions). Toute ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
592
0
55

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 821 publications
(673 citation statements)
references
References 27 publications
2
592
0
55
Order By: Relevance
“…A celebrated rigidity theorem of M. Herman [5] states that any two smooth diffeomorphisms of the circle with the same Diophantine rotation number are smoothly conjugate. Herman used purely real-variable techniques to prove this theorem.…”
Section: Introductionmentioning
confidence: 99%
“…A celebrated rigidity theorem of M. Herman [5] states that any two smooth diffeomorphisms of the circle with the same Diophantine rotation number are smoothly conjugate. Herman used purely real-variable techniques to prove this theorem.…”
Section: Introductionmentioning
confidence: 99%
“…Herman gave a refined construction in [9] of the Denjoy example of class C 1+α , for any α < 1. Recently, Sullivan has observed that renormalization methods show that there are Denjoy examples in the class C 1+Λ * , where Λ * denotes the Zygmund class (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if k ≥ 2, then for a generic subset of elements g in D ∞ there exists an increasing sequence of integers ni such that g n i converges to the identity in the C k topology. Indeed, letting dist k be a metric inducing the C k topology on Diff k + (S 1 ), the set of g ∈ D ∞ satisfying lim inf n>0 dist k (g n , Id) = 0 is a G δ -set; moreover, this set contains all g for which ρ(g) verifies a Diophantine condition [114,135,251]. One thus concludes that, for a generic g ∈ D ∞ , the sequence ( c(g n ) ) is unbounded, but it has the zero vector as an accumulation point.…”
Section: The Statement Of the Resultsmentioning
confidence: 99%
“…However, let us point out that Denjoy's theorem does not longer hold in class C 1+τ for any τ < 1. This is a consequence of a construction due to Herman [114] which we will reproduce in §4.1.4. Before passing to the proof of Theorem 3.1.1, we would like to give an "heuristic proof" which applies in a particular but very illustrative case.…”
Section: Dynamics Of Groups Of Diffeomorphisms 31 Denjoy's Theoremmentioning
confidence: 91%